Uso de hemocomponentes en el servicio de clínica del Hospital General Teófilo Dávila - Nagua Pineda, Angie Lizbeth (Machala : Universidad Técnica de Machala, 2019)
The use of blood components contributes to the oxygenation of tissues, the replacement of blood loss and the normalization of coagulation defects, therefore, transfusion requires adequate indications to avoid unnecessary risks, the objective is to determine the use of blood components in the blood Clinical service of the Teófilo Dávila General Hospital. This is a descriptive, quantitative, cross-sectional study, not experimental, based on the review of current scientific articles and guidelines of the Ministry of Public Health, in addition to the analysis of the transfusion requests of 77 patients issued by the clinic's service Hospital General Teófilo Dávila and referred to the Transfusion Medicine service in November and December 2018. It was determined that the main cause of transfusion is anemia, which represents 70.1% while qualitative platelet defects represent 2.6%, as background the Human Immunodeficiency Virus and Chronic Renal Insufficiency are reported in a higher percentage corresponding to 22% and 16.9% of the patients respectively; the age group most frequently requesting transfusion are young adults (20-64 years), predominantly male, with 53.2%, and 70.1% of patients have received previous transfusions without presenting adverse reactions; The hemocomponent that is mostly transfused is the red blood cell concentrate in 35.1%, the blood group ORH + being the most requested and, according to laboratory data, hemoglobin referential values <8g / dl with 70.1% for the transfusion of blood components.
El uso de hemocomponentes contribuye a la oxigenación de los tejidos, la reposición de pérdidas sanguíneas y la normalización de defectos de la coagulación, por lo tanto, la transfusión requiere indicaciones adecuadas para evitar riesgos innecesarios, el objetivo es determinar el uso de hemocomponentes en el servicio de clínica del Hospital General Teófilo Dávila. Se trata de un estudio descriptivo, cuantitativo, de corte transversal, no experimental, basado en la revisión de artículos científicos y guías vigentes del Ministerio de Salud Pública, además del análisis de las solicitudes de transfusión de 77 pacientes emitidas por el servicio de clínica del Hospital General Teófilo Dávila y referidas al servicio de Medicina Transfusional del mes de noviembre y diciembre del 2018. Se determinó que la principal causa de transfusión es la anemia que representa el 70.1% mientras que los defectos cualitativos de plaquetas representan el 2.6%, como antecedente se reporta el Virus de la Inmunodeficiencia Humana y la Insuficiencia Renal Crónica en mayor porcentaje correspondiente al 22% y 16.9% de los pacientes respectivamente; el grupo etario que con mayor frecuencia solicita la transfusión son los adultos jóvenes (20-64 años) predominando el sexo masculino con un 53.2%, además el 70.1% de los pacientes ha recibido transfusiones anteriores sin presentar reacciones adversas; el hemocomponente que mayoritariamente se transfunde es el concentrado de glóbulos rojos en un 35.1% siendo el grupo sanguíneo ORH+ el más solicitado y según datos de laboratorio destacan valores referenciales de hemoglobina <8g/dl con un 70.1% para la transfusión de componentes sanguíneos.
Keywords: HEMOCOMPONENTES; ANEMIA; TRANSFUSION; SERVICIO DE CLINICA